MULTIMODAL IMAGING AND TREATMENT OF SYPHILITIC CHOROIDAL NEOVASCULARIZATION. Issue Volume 16:Issues 1(2022) (January 2022) - Giuffrè, Chiara; Marchese, Alessandro; Cicinelli, Maria Vittoria; Miserocchi, Elisabetta; Querques, Giuseppe; Bandello, Francesco; Modorati, Giulio
Abstract : Purpose: To report a rare case of choroidal neovascularization (CNV) developed 2 years after successful treatment of ocular syphilis, identified by optical coherence tomography angiography. Methods: Case report. Results: A 31-year-old man with a history of syphilitic chorioretinitis developed a CNV 2 years after clinical remission of the infection. Structural optical coherence tomography (OCT) and optical coherence tomography angiography were helpful in providing detailed evidence of an extrafoveal CNV in an easy and noninvasive way. In comparison, the identification of CNV on fluorescein angiography was difficult because of the retinal blood barrier breakdown and intense choroidal background fluorescence for diffuse chorioretinal scarring of syphilitic chorioretinitis. The patient underwent 3 intravitreal injections of anti–vascular endothelial growth factor in addition to 25 mg/day of oral prednisone, with the restoration of previous visual acuity. Conclusion: Choroidal neovascularization is a rare, but sight-threatening complication of syphilitic chorioretinitis. The combination of different imaging modalities, and in particular optical coherence tomography angiography, allowed reaching a definite diagnosis of CNV. Combined treatment of systemic steroid and intravitreal anti–vascular endothelial growth factor was effective in controlling the CNV and improving the visual outcome. Abstract : Choroidal neovascularization is an extremely rare complication of syphilitic chorioretinitis. Herein, we illustrate the importance of multimodal imaging, particularly optical coherence tomography angiography, to detect the presence of choroidal neovascularization associated with syphilitic chorioretinitis. We also illustrate the clinical course after treatment.